Początki mowy u małych dzieci w koncepcjach rzymskich intelektualistów, Augustyna i Jana Chryzostoma - Jundziłł, Juliusz (Vox Patrum, 2009)
The paper is a preliminary outline of the history of views on the teaching of speech to children in ancient thinkers, especially Aristotle, Romans from the times of Republic and Empire, as well as the Church Fathers, especially Western, including Augustine in order to determine what John Chrysostom wrote and said on that subject. All the above-mentioned were not really interested in teaching speech to infants and children but in the physiology of this phenomenon (especially Aristotle) and creating the most favorable environment for the shaping of speech through the selection of nannies and child minders. There were no attempts, as Augustine aptly wrote, to teach speech consciously; it was the child himself that had to associate the sound with its material, meaningful background through observations and repeating experiences. What is more, both moral philosophers and Church Fathers described in a friendly manner (also Chrysostom) talking to children using a special, childlike language since it pleased and still pleases adults, although spoils the way children speak. The Classic Antiquity, which took care about the proper speech and promoted (like Church Fathers) rhetoric in everyday life and science, forgot about the basics, the process of creating speech, which resulted from depreciation of the first stage of children’s life, condemned to contacts with slaves – nannies. It was only the school age that stirred up stronger emotions but, as some moral philosophers wrote, children already had speech defects, among others, because of parental consent for the language deprivation.